Navigating climate change education (CCE): A framework for implementation in Indonesia - Maisuna Kundariati; I. Ibrohim; Fatchur Rohman; Safwatun Nida; Rifka Fachrunnisa; Sarah Abdul Razak (JPBI (Jurnal Pendidikan Biologi Indonesia), 2025)
Vulnerable individuals feel the massive impact of climate change. Climate research emerged decades ago, causing severe damage to Earth. This issue leads the educational setting to tackle the causes, risks, and impacts on human civilization. The growing interest in Climate Change Education (CCE) and the obstacles associated with tackling this issue provide an opportunity to perform a systematic review to better understand the actions that can contribute to global climate change education. A semi-systematic literature review identified 28 international journal articles published between 2017-2024. These publications, retrieved online from the Scopus database, created a foundation for searching for CCE objectives and contextual focuses. This study also reviewed Indonesian curriculum documents to determine the appropriate place for implementing climate change education. Through this study, we found that CCE became the primary focus of discourse around the world with the desired learning objectives. Based on a review of the Indonesian curriculum, the CCE can be integrated into science, biology, physics, chemistry, and geography. Nevertheless, it has become necessary for educational policy makers to create a CCE map that includes the subject, topics, and audience.